2015
DOI: 10.1371/journal.pone.0122441
|View full text |Cite
|
Sign up to set email alerts
|

Keratometric Index Obtained by Fourier-Domain Optical Coherence Tomography

Abstract: PurposeTo determine the keratometric indices calculated based on parameters obtained by Fourier-domain optical coherence tomography (FD-OCT).MethodsThe ratio of anterior corneal curvature to posterior corneal curvature (Ratio) and keratometric index (N) were calculated within central 3 mm zone with the RTVue FD-OCT (RTVue, Optovue, Inc.) in 186 untreated eyes, 60 post-LASIK/PRK eyes, and 39 keratoconus eyes. The total corneal powers were calculated using different keratometric indices: Kcal based on the mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Moreover, in another study using SS-OCT, Xie et al [ 18 ] found that CCT was 547.56 µm, which is almost identical to the value reported in the present study (546.65 µm) [ 19 ]. Furthermore, Hua et al [ 20 ] analyzed mean CCT and certain corneal parameters using RTVue (FD-OCT); although their CCT value (544.98 ± 33.09 µm) was comparable to our value (546.65 ± 28.69) [ 20 ], they did not evaluate sex-specific differences in this parameter. The Namil study was a multicenter study including patients over 40 years of age who were residents of central South Korea; in that study, mean CCT was slightly low (530.9 µm), but this parameter was significantly different between sexes, being 5.9 µm thicker in males ( p = 0.001) [ 21 ].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Moreover, in another study using SS-OCT, Xie et al [ 18 ] found that CCT was 547.56 µm, which is almost identical to the value reported in the present study (546.65 µm) [ 19 ]. Furthermore, Hua et al [ 20 ] analyzed mean CCT and certain corneal parameters using RTVue (FD-OCT); although their CCT value (544.98 ± 33.09 µm) was comparable to our value (546.65 ± 28.69) [ 20 ], they did not evaluate sex-specific differences in this parameter. The Namil study was a multicenter study including patients over 40 years of age who were residents of central South Korea; in that study, mean CCT was slightly low (530.9 µm), but this parameter was significantly different between sexes, being 5.9 µm thicker in males ( p = 0.001) [ 21 ].…”
Section: Discussioncontrasting
confidence: 83%
“…In a similar study using RTVue, this value for the 3 mm central circle was significantly lower (by 1.21 D), which is not consistent with the results of the present study [ 23 ].The results of Fourier indices of corneal parameters obtained in the present study are partly consistent with those obtained in a study by Tanabe et al [ 24 ], who calculated the above parameters using Fourier analysis on the basis of images obtained with videokeratography; the mean values of the four main parameters, namely spherical power, regular astigmatism, asymmetry, and higher-order irregularities, were 43.97, 0.5, 0.35, and 0.11 D, respectively, in Tanabe et al’s study [ 24 ] and 43.09, 0.5, 0.24, and 0.15 D, respectively, in our study. Hua et al [ 20 ] also assessed the mean power of the cornea using RTVue. For the 3 mm central circle, the power was 43.01 ± 1.53 D, which is practically identical to the value obtained in the present study (43.09 ± 1.27 D).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the corneal curvature, Placido-disc based topography techniques with 9 rings each 256 points in a 5.5-mm zone are projected onto the cornea, and corneal curvature of 2-mm, 2.5-mm and 3-mm central corneal zone can be obtained[ 15 ]. The standard keratometric index of 1.3375 is used for calculating the keratometer readings[ 26 , 27 ]. In the present study, the AL, CCT, ACD, PD, LT, CD and keratometer readings data of the 2.5 mm zone for each scan were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The contact lens base curve was then computed using the standard formula used for children and adults where the index of refraction of the cornea and index of refraction of air were constant values. 7 The higher CCC measurement was represented by the K1 taken from the handheld auto keratometer. There is an inverse relationship between K1 and base curve.…”
Section: Methodsmentioning
confidence: 99%